Efficiency of Neobank Activities in the Context of Their Profitability - SHKOLNYK, Inna; AKOPIAN, Darina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article addresses the development of neobanks as a new business model in the banking industry, posing as a competitor to traditional banking models. The research aims to define the theoretical foundations of neobank functioning and identify sources for enhancing neobanks’ profitability. The article analyses existing interpretations of the term "neobank" and proposes its formulation. If during the launch period and the first 3-4 years, the primary focus is directed towards scaling the operations of Neobank and establishing a substantial client base, then upon achieving these objectives, the emphasis shifts towards the necessity of profit generation. Indeed, achieving profitability constitutes a challenging endeavour for most neobanks in the current stage. The article highlights and characterises the business models of neobanks in the context of their primary revenue sources: interchange fees, income from paid subscriptions, revenue from credit activities, earnings from international transfers, and revenue from providing Banking-as-a-Service. The efficiency of operations of five European neobanks has been analysed based on their statistical reports, focusing on the dynamics of losses and profits. It was found that several large neobanks did not reach profitability by the beginning of 2022, and possible reasons for this phenomenon were identified. The primary revenue sources of the European bank Revolut have been analyzed, using it as a case study. These revenue sources include subscription revenue, payment, and commission revenue, foreign exchange, and capital operation revenue. Additionally, their structural proportions have been examined. The structural composition of various revenue sources reflects the bank’s current strategy. It can serve as a basis for modifying and optimizing services to achieve competitive advantages. Using the example of the neobank Revolut, it was found that rapid growth in revenue from foreign exchange and capital operations, along with moderate growth in other categories, contributed to a shift in the revenue structure and facilitated the attainment of profitability for the neobank. The article suggests vectors for future neobank development to increase revenue and achieve profitability.